Secondary new particle formation in Northern Finland Pallas site between the years 2000 and 2010 - Asmi, E.; Kivekäs, N.; Kerminen, V.-M.; Komppula, M.; Hyvärinen, A.-P.; Hatakka, J.; Viisanen, Y.; Lihavainen, H. (Atmospheric Chemistry and Physics, 2011)
Secondary new particle formation affects atmospheric aerosol and cloud droplet numbers and thereby, the aerosol effects on climate. In this paper, the frequency of nucleation events and the associated particle formation and growth rates, along with their seasonal variation, was analysed based on over ten years of aerosol measurements conducted at the Pallas GAW station in northern Finland. The long-term measurements also allowed a detailed examination of factors possibly favouring or suppressing particle formation. Effects of meteorological parameters and air mass properties as well as vapour sources and sinks for particle formation frequency and event parameters were inspected. In addition, the potential of secondary particle formation to increase the concentration of cloud condensation nuclei (CCN) sized particles was examined. Findings from these long-term measurements confirmed previous observations: event frequency peaked in spring and the highest growth rates were observed in summer, affiliated with increased biogenic activity. Events were almost exclusively observed in marine air masses on sunny cloud-free days. A low vapour sink by the background particle population as well as an elevated sulphuric acid concentration were found to favour particle formation. These were also conditions taking place most likely in marine air masses. Inter-annual trend showed a minimum in event frequency in 2003, when also the smallest annual median of growth rate was observed. This gives further evidence of the importance and sensitivity of particle formation for the condensing vapour concentrations at Pallas site. The particle formation was observed to increase CCN80 (>80 nm particle number) concentrations especially in summer and autumn seasons when the growth rates were the highest. When the growing mode exceeded the selected 80 nm limit, on average in those cases, 211 ± 114% increase of CCN80 concentrations was observed.